Prognostic value of TNF-α, PCT, IL-8, and HBP, combined with APACHE II score in patients with sepsis - Guo, Shuping; Liao, Chunyan; Liu, Qinghong (The Journal of Infection in Developing Countries, 2025)
Introduction: This study evaluated the prognostic value of serum cytokines tumor necrosis factor-alpha (TNF-α), procalcitonin (PCT), interleukin-8 (IL-8), and heparin binding protein (HBP); combined with acute physiology and chronic health evaluation II (APACHE II) score in sepsis patients. Methodology: Patients were divided into sepsis and septic shock groups based on sepsis-3 criteria, with non-sepsis individuals as controls. Serum TNF-α, PCT, IL-8, and HBP levels; and APACHE II scores were recorded upon intensive care unit (ICU) admission. The diagnostic value was evaluated using receiver operating characteristic (ROC) curves and areas under the curves (AUCs). Results: Correlation analysis revealed that serum TNF-α (r = 0.701), PCT (r = 0.623), IL-8 (r = 0.617), and HBP (r = 0.721) were positively correlated with the APACHE II score (p < 0.05). Serum TNF-α, PCT, IL-8, HBP levels, and APACHE II scores were significantly higher in non-survivors than survivors (p < 0.05). The AUC for combined indicators in predicting mortality was 0.913 (confidence interval, CI: 0.861–0.912), significantly higher than individual indicators. HBP showed AUC of 0.798 (CI: 0.707–0.879) and APACHE II 0.769 (CI: 0.782–0.892). The combined prediction demonstrated 96.21% sensitivity and 79.34% specificity. Conclusions: Serum TNF-α, PCT, IL-8, and HBP levels influenced sepsis patient prognosis, and their combined detection with APACHE II score provided a high predictive value for patient outcomes.